Pengembangan Media Pembelajaran Tiga Dimensi Pada Perawatan Mesin O360 Lycoming Pada Mata Kuliah Piston Engine Prodi Teknologi Perawatan Pesawat Udara - Hendri Louis Latif; Ade Sieva Perwara; Dame Artha Marbun; Muhammad Reza Fahlevi (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2022)
Three-dimension learning media has been widely used in the field of education by displaying visualizations of an object to increase the cognitive understanding of cadets and increase the imagination of cadets towards an object. Augmented reality became the basis for the development of 3D learning media. Applications in augmented reality are designed with various stages such as creating 3D objects, creating animations, creating markers, coding processes, creating augmented reality applications, and application design results.  Testing this augmented reality application uses black box testing and usability testing methods. Where in black box testing, testing was carried out on the functionality of application features, and usability testing was carried out by filling out questionnaires on 20 respondents, namely Aircraft Maintenance Technology cadets about the learning material for the O360 Lycoming engine piston course. The effectiveness of the application was tested by conducting pre-tests and post-tests on respondents, with the average pre-test score being 53.5 and the average post-test score being 92.5. Thus, it can be concluded that augmented reality technology in the development of 3D learning media can improve cadet learning outcomes and improve cadets' performance and skills